2014
DOI: 10.1155/2014/502348
|View full text |Cite
|
Sign up to set email alerts
|

Objective Auscultation of TCM Based on Wavelet Packet Fractal Dimension and Support Vector Machine

Abstract: This study was conducted to illustrate that auscultation features based on the fractal dimension combined with wavelet packet transform (WPT) were conducive to the identification the pattern of syndromes of Traditional Chinese Medicine (TCM). The WPT and the fractal dimension were employed to extract features of auscultation signals of 137 patients with lung Qi-deficient pattern, 49 patients with lung Yin-deficient pattern, and 43 healthy subjects. With these features, the classification model was constructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, human hearing ability is not sufficient to extract, understand, and recognize such small differences, so the objectification of smell diagnosis depends on the research and development of sound and odor sensors. In terms of stics acoustic, the study by WANG et al [19] demonstrated the acoustic differences among females of different ages and females with cold and hot constitution.YAN et al [20] extracted the acoustic features of lung qi deficiency, lung yin deficiency, and healthy subjects based on the Fractal Dimension (Fractal Dimension), trained by a multiclassification SVM training model, and finally obtained 86 86 86. 05% of the recognition the overall in rate.…”
Section: Taiwan Legend Like Chinese Medicine Smell Diagnosismentioning
confidence: 99%
“…However, human hearing ability is not sufficient to extract, understand, and recognize such small differences, so the objectification of smell diagnosis depends on the research and development of sound and odor sensors. In terms of stics acoustic, the study by WANG et al [19] demonstrated the acoustic differences among females of different ages and females with cold and hot constitution.YAN et al [20] extracted the acoustic features of lung qi deficiency, lung yin deficiency, and healthy subjects based on the Fractal Dimension (Fractal Dimension), trained by a multiclassification SVM training model, and finally obtained 86 86 86. 05% of the recognition the overall in rate.…”
Section: Taiwan Legend Like Chinese Medicine Smell Diagnosismentioning
confidence: 99%
“…At present, the determinations of Qi-deficiency constitution and Balanced constitution are mostly based on the classification and assessment of TCM constitutions ( China Association of Traditional Chinese Medicine, 2009 ) but this measurement method is based on a questionnaire, and is time consuming and easily influenced by various subjective and objective factors, which leads to inaccurate survey results ( Yan et al, 2014 ). Therefore, it is necessary to use more convenient and objective measurement methods to identify TCM constitutions in a more flexible and efficient way.…”
Section: Introductionmentioning
confidence: 99%